Efficacy of Lactobacillus spp. Interventions to Modulate Mood Symptoms: A Scoping Review of Clinical Trials - Diego Fernández-Rodríguez; María Consuelo Bravo; Marcela Pizarro; VERGARA BARRA, PABLO ANDRES; María José Hormazábal; Marcell Leonario-Rodriguez (MDPI AG, 2025)
Probiotics containing Lactobacillus spp. have demonstrated immunological and gastrointestinal benefits and may aid in recovery from mood disorders. However, evidence of their mood-modulating efficacy remains inconsistent. Aim: To analyze the efficacy of probiotic interventions with Lactobacillus spp. in modulating mood in humans. A scoping review was conducted following the PRISMA guidelines. A systematic search of the PubMed and Scopus databases was performed using nine Boolean combinations of the terms “mental”, “mental diseases”, “mental disorders”, “gastrointestinal microbiome”, “gut microbiome”, “gut microbiota”, and “lactobacillus”. The search was limited to clinical trials published in English and limited to ten years of publication. Eligible studies met the following criteria: (a) probiotic interventions in adults, with or without mood disturbances; (b) the use of Lactobacillus spp., either alone or in combination; (c) mood assessment instruments applied pre- and post-intervention; and (d) reporting of probiotic concentrations. Trials involving populations with other psychiatric or neurological diagnoses or those combining probiotics with additional mood-modulating nutrients were excluded. From 3291 records, 17 clinical trials met the inclusion criteria. Data extracted included the author, year, population, country of origin, probiotic strain(s), dosage, intervention mode and duration, and outcomes related to the microbial composition, biomarkers, and microbial metabolites. Trials were categorized by probiotic type (single vs. multi-species) and participant profile (healthy individuals and those with depressive symptoms or specific physiological conditions). Preliminary evidence from single-strain interventions, particularly high-dose L. plantarum administered for ≥8 weeks, suggests potential improvements in anxiety, sleep quality, and inflammatory biomarkers. Multi-species formulations yielded reductions in depressive symptoms and changes in neurobiological markers. Nonetheless, substantial heterogeneity in strains, dosages, durations, and outcome measures limited cross-study comparisons. Lactobacillus spp. interventions show promising mood-modulating potential, especially with specific strains and prolonged administration. Standardized protocols, rigorous controls, and clearly defined clinical cohorts are needed to establish robust, evidence-based recommendations.